Onychoscopy in Palmoplantar Psoriasis: A Comparative Study of Nonpustular Palmoplantar Psoriasis and Palmoplantar Pustulosis - Ahu Yorulmaz (Mattioli1885, 2024)
Introduction: Palmoplantar psoriasis (PP) is classified as nonpustular psoriasis (NPPP) or palmoplantar pustulosis (PPP). Objective: We sought to shed light on the phenotypic diversity of nail psoriasis (NP) and conducted a thorough study of the dermoscopic features of nail lesions from patients with NPPP and PPP. Methods: A prospective study included 35 patients with NPPP and 20 patients with PPP who had macroscopic NP changes in at least three of their nails. Demographic and clinical data, such as general characteristics, history, a thorough dermatological examination, and musculoskeletal assessment, were recorded. Each patient had their nails evaluated with video dermoscopy. The statistical analysis was carried out using SPSS software, including descriptive and analytical statistics. Results: Dermoscopic patterns of nail lesions in both groups differed from those seen in psoriasis vulgaris (PV). Trachyonychia was the most common dermoscopic pattern among NPPP patients. Nail bed pustules were found in 75% of the PPP patients, and they were the most common dermoscopic finding identifying PPP nail lesions. In comparison to the NPPP group, patients with PPP had a higher frequency of psoriatic arthritis (PsA) and higher PP and NP severity scores. In the PPP group, all patients with PsA had pustules. Conclusions: NP has a heterogeneous presentation and various clinical manifestations in NPPP, PPP, and PV. The differences in dermoscopic patterns of nail lesions among NPPP, PPP, and PV reflect the diseases' distinct characteristics. A thorough dermoscopic examination of the nails may reveal information about both the underlying pathophysiological pathways and the overall course of psoriasis.